Penggunaan Media Sosial untuk Kampanye Baca: Mendukung Literasi Anak Indonesia - Aripin, Nurasma; Sitompul, Siti Jahria; Jonsa, Alimas (Lok Seva: Journal of Contemporary Community Service, 2024)
The low literacy ability of Indonesian children is the responsibility of all parties. In simple terms, Literacy can be interpreted as skills in writing and reading. Low reading ability is influenced by access to difficult books and very limited ownership of reading books. The condition of low reading literacy of Indonesian children was then summarized in an Anthology book entitled "Jejak Juang Laskar Literasi" by alumni education volunteers of the Indonesian Literacy School Program and Gemari Baca Dompet Dhuafa. ALUSIA collaborated with academics from Teuku Umar University and literacy activists to review the book.  The method is carried out in the form of a talk show with a narrative model directly through Instagram social media. The recorded audience until December 2024 is 316 spectators. The theme raised was "Literacy at the fingertips, reading campaign for all".  The audience's response during the narration activity was good, which was measured by the enthusiasm of the audience asking questions and commenting in the comment column during the event, and also the number of spectators that continued to increase every day. This narrative activity is a form of community service as an effort to invite readers from all walks of life so that the literacy of Indonesian children increases.